SOCIALIZATION OF THE USE OF VEGETABLE WASTE IN NAWANGSASI VILLAGE FOR ANIMAL FEED IN THE FORM OF SILAGE - Ferdi Oktavi; Mu'awiyatu Al-laitsi; Muhammad Arif Fadilah; Lia Aseptin Murdini; Apep Senses Saputra (Jurnal Abdisci, 2026)
Abstract: Background: The problem of organic waste, especially that derived from vegetables, is a relatively important environmental issue. The accumulation of waste without proper treatment can cause pollution, unpleasant odors, and become a breeding ground for pests and diseases. Aim: a waste management strategy that is environmentally friendly and can also provide economic benefits for the village community. One innovative solution that can be implemented is to process vegetable waste into animal feed in the form of silage. Methods: The initial stage of vegetable waste inventory in Nawangsasi village, followed by silage formulation and testing its use for animal feed. Results: Silage formula was obtained by utilizing organic waste., Conclusions: The use of vegetable waste in Nawangsasi Village as animal feed in the form of silage demonstrates excellent potential to address the issue of organic waste while enhancing local feed resilience. Nawangsasi Village generates a considerable amount of vegetable waste from agricultural and market activities, which was previously often disposed of without proper control, resulting in environmental pollution. Involvement. The silage formula can be applied to farmers.